Principal's Managerial Leadership in Improving School Quality in Senior High Schools - Aburrohman, Muhamad Afif; Hidayati, Dian; Sukirman, Sukirman (Tadbir : Jurnal Studi Manajemen Pendidikan, 2025)
The principal is a critical factor in the school's quality and plays a significant role as a leader. A principal must possess managerial skills to effectively lead and manage an educational institution. The impetus for this study is the necessity to enhance the quality of the school. This study, therefore, aims to ascertain the extent to which the principal's managerial leadership contributes to improving the school's quality. This qualitative research employed a qualitative descriptive method. Interviews, documentation, and observations were implemented as data collection techniques. The Principal, Vice Principal for Public Relations, Vice Principal for Curriculum, Vice Principal for Student Affairs, Vice Principal for Al-Islam, Muhammadiyah, and Arabic (ISMUBA), and Vice Principal for Infrastructure were all participants in this study. Using guidelines on source and technical triangulation, data analysis was then carried out using qualitative descriptive techniques. The results of this study revealed that to effectively lead the school in enhancing its quality, a principal must possess managerial leadership skills: 1) conceptual skills, 2) humanitarian skills, and 3) technical skills.